Influence of cognitive impairment on rehabilitation received and its mediating effect on functional recovery - Dutzi, Ilona; Schwenk, Michael; Kirchner, Marietta; Jooss, Eva; Bauer, Jürgen M.; Hauer, Klaus (Journal of Alzheimer's disease, 2021)
Background: Cognitive impairment (CI) has been reported to negatively impact rehabilitation outcomes. Knowledge about differences in rehabilitation received in dependence of CI as a potential mediating factor is limited. Objective: To analyze whether
Gesehen am 23.12.2021